Assessing sexual function and vulvovaginal symptoms in young patients with vulvar dystrophy - A. G. Solopova; E. E. Achkasov; A. D. Makatsariya; I. V. Khamani; T. A. Blbulyan; V. S. Moskvichyova (Акушерство, гинекология и репродукция, 2021)
Aim: to comparatively assess sexual function and intensity of vulvovaginal symptoms in patients with vulvar lichen sclerosus and mixed vulvar dystrophy. Materials and Methods. There were examined 57 patients with vulvar lichen sclerosus and 63 patients with mixed vulvar dystrophy, with mean patient age 35.0 ± 0.6 (18–45) years. Prior to therapy, the study participants completed the Female Sexual Function Index (FSFI) and the Vulvovaginal Symptoms Questionnaire (VSQ). Results. Severe sexual dysfunction (FSFI score 2) was detected in 14 % of cases (n = 8) in group 1 (sclerotic lichen vulva) and 17 % (n = 11) in group 2 (mixed dystrophy). Remaining respondents had total score below the normal cut-off. The mean FSFI score for group 1 and 2 was 17.68 and 16.78, respectively. VSQ testing found that most common complaint in both groups was itching (91 and 95 %, respectively). The majority of patients also noted a deteriorated emotional state and disease-related limitations in everyday life. The maximum VSQ score was 20 corresponding to the peak negative disease impact found in 23 % and 37 % patients in group 1 (n = 13) and group 2 (n = 23), respectively. Many patients also noted lack of lubrication most likely associated with discomfort and pain during intercourse, as well as worsened relationship with partner. Conclusion. The vulvar dystrophy negatively affects sexual function in young women. Symptoms typical to such conditions impose marked restrictions on intimate life, relationships and quality of general life. It accounts for why it is important to include questionnaires in the set of measures to assess sexual function and vulvovaginal symptoms both before and after treatment.